#TITLE_ALTERNATIVE# - YATHA PRADIPTA (NIM 15107054); Pembimbing: Dr. rer. nat. Wiwin Windupranata, ST, M.Si., dan Dr., GEDE
Tidal observations have a lot of benefit in geodetic engineeringespecially to determine the vertical datum for bathymetri. Vertical datum that ussually used for reference aremean sea level and chart datum. At firsttidal observations done by measuring the height of waterthat indicated by numbers on tidepole, along with the development of satellite altimetry to observe the water level without direct measurements and cover a larger area. The result from data analysis that obtained from satellite altimetry observations are collected so it can be formed a global tide models. The application of tide models still need to be verified by measurements of tidal stations to determine quality of the models. Tidal models used in this study is TPXO 7.1. Procesesinthis research are to extract the value of the amplitudes and phases from tidal harmonic constants in the model and also determine the position of chart datum tomean sea level. The results of determining the position of chart datum to mean sea levelwith the approach bytide model TPXO 7.1, at West Java Province waters indicatethat the position ofthe chartdatum to mean sea level in the northern coast smaller than the southern coast with varyingtypes oftides. Direction of the tidalwave that develop onthe north coast is fromwestto east,while the southcoast is from eastto west.